Leveraging Technology for Dengue Fever Management Using Mobile Health GIS and Big Data to Improve Epidemic Control in Tropical Regions: A Literature Review - Nabilla Salsabilla Zainudin, Alifia; Prawiragara, Fachrizal Arfani (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Dengue Fever (DBD) remains a major public health issue in tropical countries, including Indonesia, leading to significant morbidity and mortality, particularly among children and young adults. With the increasing number of outbreaks, innovative approaches are necessary for effective management. Technological advancements, including mobile health applications (mHealth), Geographic Information Systems (GIS), and big data analytics, have been identified as valuable tools in the early detection, monitoring, and control of Dengue Fever. These technologies promise to improve the efficiency of health systems and expedite the response to outbreaks.Objective: This study aims to explore the role of technology in managing Dengue Fever outbreaks, focusing on the application of mHealth, GIS, and big data in enhancing public health responses and epidemic control efforts.Methods: A literature review was conducted using databases such as PubMed, Google Scholar, and Scopus, with keywords including